2012
DOI: 10.2139/ssrn.1402891
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Strategic Voting

Abstract: We estimate a model of strategic voting by adopting a recently developed inequality-based estimator in a discrete-choice framework. The di¢ culty of identi…cation comes from the fact that preference and voting behavior do not necessarily have a one-to-one correspondence for strategic voters. We obtain partial identi…cation of preference parameters from the restriction that voting for the least-preferred candidate is a weakly dominated strategy. The extent of strategic voting is identi…ed using variation genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
(45 reference statements)
0
27
1
Order By: Relevance
“…A second strand of the literature relies on aggregate electoral results and studies strategic voting by imposing assumptions on the mapping between voters' preferences and vote choices. Kawai and Watanabe (2013) and Myatt and Fisher (2002) calibrated structural models to estimate the number of voters who did not vote for their preferred candidate and the impact of strategic voting on the number of seats won by a party, respectively. In the context of the German split-ticket voting system, Spenkuch (2018) compared votes cast for party lists under a proportional rule with votes cast for individual candidates under plurality rule, and reported that about one third of voters behave strategically (also see Spenkuch (2015)).…”
Section: Contribution To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A second strand of the literature relies on aggregate electoral results and studies strategic voting by imposing assumptions on the mapping between voters' preferences and vote choices. Kawai and Watanabe (2013) and Myatt and Fisher (2002) calibrated structural models to estimate the number of voters who did not vote for their preferred candidate and the impact of strategic voting on the number of seats won by a party, respectively. In the context of the German split-ticket voting system, Spenkuch (2018) compared votes cast for party lists under a proportional rule with votes cast for individual candidates under plurality rule, and reported that about one third of voters behave strategically (also see Spenkuch (2015)).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Alternatively, each voter's choice to behave strategically or expressively when choosing a candidate and deciding whether to vote or abstain could be endogenized in a full-fledged model of costly voting in elections with more than two candidates. Future work along these lines could build on Shayo and Harel (2012), whose theoretical framework includes a tradeoff between instrumental and non-instrumental voting motives, and on Kawai and Watanabe (2013) and Fisher and Myatt (2017), who introduced a share of sincere voters in rational models of vote choice.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before outlining our approach, we emphasize that our inference method is not only of theoretical interest-it is applicable to a number of empirical models in the literature. These models include: entry games with multiple Nash equilibria (Bresnahan andReiss (1990, 1991), Berry (1992), Jia (2008), Ciliberto and Tamer (2009); 2 first-price auctions (Haile and Tamer (2003)); innovation and product variety (Eizenberg (2014)); sincere versus strategic voting (Kawai and Watanabe (2013)); municipal mergers (Weese (2015)); discrete-choice with social interactions (Soetevent and Kooreman (2007)); matching with externalities (Uetake and Wanatabe (2012)); and friendship networks (Miyauchi (2014)). In these models, incomplete structures arise for different reasons.…”
Section: Objectives and Outlinementioning
confidence: 99%
“…Likewise, this assumption has also been justified for complex voting rules such as the Alternative Vote Rule (Bartholdi and Orlin 1991;Straeten et al 2010). However, there are voting situations, such as board and committee meetings, and less complex voting rules, especially the Plurality Rule, for which sincere voting is not an adequate behavioral assumption, as empirical and experimental evidence suggest (e.g., Straeten et al 2010;Kawai and Watanabe 2013). How do the various voting rules compare under strategic voting behavior?…”
Section: Strategic Votingmentioning
confidence: 99%